2023
DOI: 10.1038/s41598-023-32076-8
|View full text |Cite
|
Sign up to set email alerts
|

Partner separation rescues pair bond-induced decreases in hypothalamic oxytocin neural densities

Abstract: Studies in prairie voles (Microtus ochrogaster) have shown that although formation of the pair bond is accompanied by a suite of behavioral changes, a bond between two voles can dissolve and individuals can form new pair bonds with other conspecifics. However, the neural mechanisms underlying this behavioral flexibility have not been well-studied. Here we examine plasticity of nonapeptide, vasopressin (VP) and oxytocin (OT), neuronal populations in relation to bonding and the dissolution of bonds. Using adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Females display a host of isolation-induced phenotypes, including anhedonia, increased anxiety-like phenotypes and aggression, and neuroendocrine disruption (Grippo et al, 2008, 2007; McNeal et al, 2014; Scotti et al, 2015; Watanasriyakul et al, 2022). One study reported persistence of pair bonds following 4 wks separation, without any effect of sex in ∼2-6 month old voles (Fricker et al, 2023). In our experiments, partner preference after 4 wks separation followed a U-curve, where 6- and 18-month females demonstrated a strong partner preference, but 12-month animals did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Females display a host of isolation-induced phenotypes, including anhedonia, increased anxiety-like phenotypes and aggression, and neuroendocrine disruption (Grippo et al, 2008, 2007; McNeal et al, 2014; Scotti et al, 2015; Watanasriyakul et al, 2022). One study reported persistence of pair bonds following 4 wks separation, without any effect of sex in ∼2-6 month old voles (Fricker et al, 2023). In our experiments, partner preference after 4 wks separation followed a U-curve, where 6- and 18-month females demonstrated a strong partner preference, but 12-month animals did not.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, direct manipulation of these circuits can facilitate or inhibit pair bonding in prairie voles, and can even produce bonding in typically promiscuous species (Keebaugh et al, 2015; Lim et al, 2004; Lim and Young, 2004; Ross et al, 2009; Winslow et al, 1993; Young et al, 2001). Dynamic changes in oxytocin and vasopressin circuitry occur across postnatal development and in response to pair bonding, pup rearing, and partner separation (Audunsdottir and Quintana, 2022; Ebner et al, 2013; Fliers et al, 1985; Fricker et al, 2023; Hiura et al, 2023; Hiura and Ophir, 2018; Ishunina and Swaab, 1999; Kelly et al, 2018, 2017; Kenkel et al, 2019). However, the vast majority of experimentation on pair bonding and its component neurochemical systems is performed in young adult voles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Males and females who were paired for 2 or more weeks prior to separation retained their partner preference for at least 4 weeks of separation. 49,120 For shorter pairing periods, pair bonds were not always retained. 54,121 In tests that enable short, repeated rounds of partner or novel interaction after 4 weeks of separation, female voles with long-term bonds exhibited dramatically reduced partner-directed huddling.…”
Section: Modeling Loss Adaptation In Volesmentioning
confidence: 99%
“…49 Bonding also results in changes in oxytocin systems that revert upon long-term separation. 54,120 In both male and female voles, partner separation increases the number of oxytocin immunoreactive cells in the periventricular nucleus to the level of sexually naïve same-sex sibling pairs. 120 This remodeling of social reward systems may ultimately be key indicators of loss adaptation.…”
Section: Modeling Loss Adaptation In Volesmentioning
confidence: 99%